Factors Affecting China’s Tea Exports to Malaysia - Yanqi, Hu (Universiti Malaysia Sarawak, 2025)
This study aims to explore the factors affecting China’s tea exports to Malaysia and their long-term and short-term dynamic impacts, so as to deepen China-Malaysia trade relations. Based on demand theory, this study mainly adopts the Autoregressive Distributed Lag (ARDL) approach to conduct an empirical analysis using quarterly data from 2005 to 2024. It focuses on examining the impacts of variables such as the price of China’s tea imported by Malaysia, the price of coffee imported by Malaysia, Malaysia’s GDP, Malaysia’s tea production, and international oil price on the export volume. The empirical results show that an increase in the price of China’s tea significantly inhibits export volume in the long-term. As a substitute, coffee price exhibits a significantly negative impact in the long-term, indicating that tea and coffee in Malaysia do not have a conventional substitution relationship. Malaysia’s GDP has a significantly positive impact in the long-term, while local tea production and international oil price exert significantly negative long-term impact on China’s tea exports. The findings from Granger causality test further indicate that the price of China’s tea, the price of coffee, and GDP of Malaysia can Granger cause the China’s tea exports to Malaysia in the short-run. This study provides targeted reference suggestions for enterprises and policymakers to promote the development of China-Malaysia tea trade, filling the gap in the literature.